The Relationship Between Oil Palm Harvest Premium and Employee Performance at Palm Oil Company - Jubelina F Simanjuntak; Natelda Rosaldiah Timisela; Ester Dorina Leatemia (Jurnal Social Economic of Agriculture, 2023)
Today's business competition is getting tougher so that employees are required to maintain and improve their performance. Therefore, the Company needs to maintain employee motivation and performance. This study aims to determine the prevailing system of oil palm harvest fees and the relationship between oil palm harvest fees and employee performance. This study uses a descriptive approach and Pearson product-moment analysis to determine the relationship between premium and performance. The results showed that the harvest premium system that applies is a wholesale system with a stipulation of 120 janjang/HK and a premium value of Rp. 100,-. Based on the factors of work quantity, work quality, and attendance, it shows that the harvest premium has a strong and significant relationship as indicated by the correlation value between the harvest premium and employee performance based on the quantity of work. 0.720. Harvest premium with employee performance based on work quality is 0.598 and the correlation between harvest premium and employee performance based on attendance is 0.605.